Three-bladed horizontal axis water turbine simulations with free surface effects - Rodríguez, L.; Lain, Santiago; Benavides-Moran, Aldo (Zielona Góra: Uniwersytet Zielonogórski)
In this work, the influence of the free surface on the performance of a three bladed horizontal-axis turbine is explored by means of a three-dimensional, transient, two-phase flow computational model implemented in the commercial CFD software ANSYS Fluent 19.0.
Keywords: hydrokinetic turbine; VOF; sliding mesh; torque coefficient